Rib'ah: The Concept of Local Tradition Guarantee in Early Islam - Natsir, Ahmad; Muzakki, Hawwin; Ulfa, Diana Lutfiana (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This article aims to express a word in the Sahifah Yathrib (Medinah Charter), namely rib'ah. This word contains quite a crucial meaning, however, it is rarely used daily by academics. Meanwhile in Indonesia, religious practices of peace and moderation still experience quite dangerous obstacles in society. All destruction of religious facilities, traditions, and even opposing cultures adhered to by the majority. This research is a literature study using the ma'na cum maghza framework initiated by SahironSyamsudin. With this framework, this research produces three main conclusions, namely: first, rib'ah has the basic meaning of dividing the spoils of war. However, in practice, the Prophet Muhammad guaranteed not only commerce but also religion. Second, rib'ah had its initial purpose as an effort by the Prophet Muhammad to unite the Muhajirin and Ansar, as well as for the development of a stable country. Third, the guarantee of freedom of religion and belief contained in this word can be used as a basis for hifz al-din, which means protection of security and comfort for a person to freely choose their religion and belief.